Blue ocean strategy: Application in Universiti Sains Malaysia library - Basri, Jamilah Hassan; Ghadzali, Mohd Pisol; Ismail, Mohd Ikhwan (Persatuan Pustakawan Malaysia, 2011)
The Blue Ocean strategy was developed by W.C. Kim and R. Mauborgne. It is relatively new and was only introduced in 2004, where its recommends looking at the market boundaries differently and formulating products or services to customers from different segments. Organizations such as libraries should raise the standard of activities higher than the common standard and offer customers higher values than their competitors. In other words, libraries need to deliver value at low cost and simultaneously they need to reduce and eliminate other insignificant activities. This paper focuses on several tools and models of the Blue Ocean strategy namely the “Eliminate-Reduce-Raise-Create Grid” model since the main key ideas fall under the “Create Grid” where the innovative value takes place, as well as to create unique values for customers. Thus, the application of this model at the Universiti Sains Malaysia (USM) Library is vital in the provision of successful customer service, best quality and satisfying products. The Blue Ocean strategy is also the most appropriate strategy for libraries whose services are mature and usually in the declining phase of the service life cycle with decreasing customer loyalty.